Higher Glycemic Excursion of Newly Diagnosed Youthonset Type-2 Diabetes Mellitus May Be Related to Â-Cell Secretory Capacity and Not to Insulin Resistance (Bangladesh Journal of Medicine, 2023)
Background: Youth-onset type 2 Diabetes mellitus (T2DM) often presents with high glycemic values.To see the plasma glucose and hemoglobin A1c (HBA1c) at diagnosis and their relationship with â-cell secretory capacity and insulin resistance in phenotypic T2DM of young.Methods: This cross-sectional study enrolled 72 newlydiagnosed youth-onset phenotypically T2DM [age range 19-29, median 27, inter-quartile range (IQR) 24-29 years; male 32 (44.4%), female 40 (55.6%)] during March-December’2022 in Endocrinology department, BSMMU. The secretory capacity of â-cell was estimated by fasting C-peptide (measured by chemiluminescence immunoassay) and insulin resistance by calculating visceral adiposity index (VAI) and serum triglyceride/highdensity lipoprotein (TH/HDL) ratio.Results: Median HbA1c, fasting plasma glucose (FPG), and 2h plasma glucose (2h-PG) of the participants were 8.7% (IQR 6.7-11.0), 10.8 (IQR 7.1-16.3) mmol/L and 18.0 (IQR 13.1- 24.3) mmol/L respectively. All glycemic values were negatively correlated to fasting C-peptide (HbA1c: r=-0.437, p